Corrigendum to "Meeting the food security challenge for nine billion people in 2050: What impact on forests?" [Global Environ. Change 62 (2020) 102056]. (November 2020) - Bahar, Nur H.A.; Lo, Michaela; Sanjaya, Made; Van Vianen, Josh; Alexander, Peter; Ickowitz, Amy; Sunderland, Terry
Abstract: As the world's population continues to grow, agricultural expansion is expected to increase to meet future food demand often at the expense of other land uses. However, there are limited studies examining the degree to which forest cover will change and the underlying assumptions driving these projections. Focusing on food and forest scenarios for the middle to the end of the current century, we review 63 main scenarios and 28 global modelling studies to address variations in land use projections and evaluate the potential outcomes on forest cover. Further, their potential impacts on greenhouse gases (GHG) emission/sequestration and global temperature are explored. A majority (59%) of scenarios expected a reduction in both forests and pasturelands to make way for agricultural expansion (particularly reference and no mitigation scenarios). In most scenarios, the extent of forest loss is proportional to that of crop gain, which is associated with higher GHG emission and global temperature, loss of carbon sequestration potential and increase in soil erosion. However, 32% of scenarios predicted that meeting food security objectives is possible without leading to further deforestation if there is a global reduction in the demand for energy intensive foods, and improvements in crop yields. Forest gain and lower rates of deforestation are needed to achieve ambitious climate targets over the next decade. Our analysis also highlights carbon taxes (prices), reforestation/afforestation and bioenergy as important variables that can contribute to maintaining or increasing global forest area in the future.